Latin America ClimateSmart Villages AR4D sites: 2016 Inventory - Bonilla Findji, Osana; Álvarez Toro, Patricia; Martínez Barón, Deissy; Ortega, Luis A.; Leguía Hidalgo, Efraín José; Aguilar, A.; Paz, Liliana Patricia; Suchini, José G. (2017)
Inventory of CSA practices in Latin America’s ClimateSmart Villages.